2013
DOI: 10.1021/bi400729e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of the Pump Cycle of the KdpFABC P-Type ATPase

Abstract: The high-affinity potassium uptake system KdpFABC is a unique type Ia P-type ATPase, because it separates the sites of ATP hydrolysis and ion transport on two different subunits. KdpFABC was expressed in Escherichia coli. It was then isolated and purified to homogeneity to obtain a detergent-solubilized enzyme complex that allowed the analysis of ion binding properties. The electrogenicity and binding affinities of the ion pump for K(+) and H(+) were determined in detergent-solubilized complexes by means of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(66 citation statements)
references
References 49 publications
7
59
0
Order By: Relevance
“…With respect to pH, steady-state K þ currents were found to be maximal at pH 7.3-7.4 (Damnjanovic et al, 2013). At lower pH, binding of protons reduced the pump current and at higher pH the release of protons inhibited the electrogenic pump activity.…”
Section: Electrogenic K þ Transportmentioning
confidence: 96%
See 2 more Smart Citations
“…With respect to pH, steady-state K þ currents were found to be maximal at pH 7.3-7.4 (Damnjanovic et al, 2013). At lower pH, binding of protons reduced the pump current and at higher pH the release of protons inhibited the electrogenic pump activity.…”
Section: Electrogenic K þ Transportmentioning
confidence: 96%
“…The results indicate that these ions bind in an electrogenic manner to a site presumed to be in the membrane domain of the KdpFABC complex. The binding stoichiometry of each ion was relatively independent of the other ion, suggesting that there are independent sites (Damnjanovic et al, 2013). Studies of K þ -binding indicated that the relevant sites inside KdpA do not move relative to the dielectric field during phosphorylation and dephosphorylation reactions.…”
Section: Electrogenic Partial Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the aforementioned potassium uptake systems achieve potassium transfer into the cytoplasm only at high extracellular potassium concentrations (e.g., Damnjanovic et al, 2013). In contrast to this, three metagenomic contigs (contigs000001, contig000049, contig000055) encode an additional Kdp-type K + uptake ATPase.…”
Section: Resultsmentioning
confidence: 99%
“…The Post-Albers scheme was found to be a general mechanism valid also for all other P-type ATPases whose pump cycles were studied so far, such as the CaATPase of the sarcoplasmic reticulum (SERCA) and the gastric H,K-ATPase [11], as well as the KdpFABC ATPase [12]. P-type ATPases share an (eponymous) phosphorylated intermediate in which the γ phosphate of the ATP molecule is transferred to a highly conserved aspartate located at the P domain of the protein (see below).…”
Section: Introductionmentioning
confidence: 99%